The Psychological Impact of Domestic Violence in Medan - Alvi Syahrin; Fatwa Imelda; D.K. Dewi (Talenta Publisher, 2021)
Violence against women is any violent act towards women which results in or tends to cause physical, sexual, or psychological damage and suffering, either happened to adult women, daughters, and teenagers. It includes threatening, coercion, or limiting women's movement on purpose. Also, the violence abuses can occur in a family or a society. In fact, psychological abuse has more effect on women than physical abuse. It causes long-term reactions such as fear, anxiety, exhaustion, post-trauma stress disorder, sleeping and eating disorder. Another effect of domestic violence toward wives is reproductive health disorders causing sociological disorders. This paper brings up how to provide proper handling of domestic violence cases while many of its victims do not receive justice. The research method is conducting interviews in West Medan Precinct by using the empirical normative research method. The result is to provide proper education relating to domestic violence cases, specifically towards the victims who are affected psychologically and physically. Thus, the nurses should assist the victims either while doing medical, health, or psychological activity. Also, other parties, such as family, police, district attorney, advocates, social institutions, or protection from the court, should be active in protecting the victims from domestic violence.